2022
DOI: 10.1021/acsami.2c15015
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Wolfram-Doped Polypyrrole for Photonic Hyperthermia-Synergized Radiotherapy

Abstract: Single ionizing radiation at a tolerable dose is ineffectual in eliminating malignancies but readily generates harmful effects on surrounding normal tissues. Herein, we intelligently fabricated novel wolfram-doped polypyrrole (WPPy) through a simple oxidative polymerization method with WCl 6 as an oxidizing catalyst, which possessed good biocompatibility, high photothermal conversion, and intensive radiosensitivity capacities to concurrently serve as a photothermal reagent and a radiosensitizer for hyperthermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Benefiting from its large specific capacitance, the maximum energy density ( E max ) of BNLC‐850 SC is 14.72 Wh Kg −1 , which is higher than the E max of heteroatom‐doped porous carbon‐based symmetric supercapacitors reported in recent literature (Figure 5e). [ 30–35 ] Moreover, BNLC‐850 SC also displayed long‐cycle performance, after 10000 cycles at 10 A g −1 , the capacitance retention rate is still as high as 92.1%. (Figure 5f).…”
Section: Resultsmentioning
confidence: 99%
“…Benefiting from its large specific capacitance, the maximum energy density ( E max ) of BNLC‐850 SC is 14.72 Wh Kg −1 , which is higher than the E max of heteroatom‐doped porous carbon‐based symmetric supercapacitors reported in recent literature (Figure 5e). [ 30–35 ] Moreover, BNLC‐850 SC also displayed long‐cycle performance, after 10000 cycles at 10 A g −1 , the capacitance retention rate is still as high as 92.1%. (Figure 5f).…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 ] The peak intensities of the bending vibration of H (≈800–950 cm −1 ) and the stretching vibration of H (≈3040 cm −1 ) on the aromatic group both weakened with the increase of temperature, which indicated that the PAHs of CTP were gradually condensed (carbon with a certain degree of graphitization was gradually formed) with the increase of temperature. [ 27,28 ]…”
Section: Resultsmentioning
confidence: 99%
“…As an important conjugated polymer, polypyrrole (PPy) is characterized by a large p-electronic delocalized backbone and inter-doping with oxidant complexes and stabilizers, which confers potent photothermal and photo-electronic advantages. [16][17][18][19] These features have been widely utilized in biological applications, such as photothermal therapy (PTT), drug delivery, tissue engineering, and biosensors. [20][21][22] For instance, various PPy morphologies have been developed for near infrared (NIR) laser-mediated PTT against malignant tumors, including ultrasmall PPy smaller than 10 nm, twodimensional PPy, hollow PPy, and so on.…”
Section: Introductionmentioning
confidence: 99%